2016
DOI: 10.1002/aqc.2625
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the ice: the introduction of biofouling organisms to Antarctica on vessel hulls

Abstract: ABSTRACT1. Few reports exist that describe marine non-native species in the Southern Ocean and near-shore waters around the Antarctic continent. Nevertheless, Antarctica's isolated marine communities, which show high levels of endemism, may be vulnerable to invasion by anthropogenically introduced species from outside Antarctica via vessel hull biofouling.2. Hull surveys of the British Antarctic Survey's RRS James Clark Ross were undertaken between 2007 and 2014 at Rothera Research Station on the Antarctic Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 21 publications
1
49
1
Order By: Relevance
“…Live specimens of A. improvisus were previously found on international commercial ships arriving at Churchill (Chan et al 2015b). Our finding adds to growing evidence documenting that temperate biofouling taxa, including NIS, are capable of surviving transits in polar waters (Lewis et al 2004, 2006; Lee and Chown 2007, 2009; Chan et al 2015b; Hughes and Ashton 2016). For example, Lewis et al (2004) found 72% of original biofouling assemblage, including invasive taxa, survived a voyage from Western Australia to Heard Island (sub-Antarctic) and then back to Australia (Tasmania).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Live specimens of A. improvisus were previously found on international commercial ships arriving at Churchill (Chan et al 2015b). Our finding adds to growing evidence documenting that temperate biofouling taxa, including NIS, are capable of surviving transits in polar waters (Lewis et al 2004, 2006; Lee and Chown 2007, 2009; Chan et al 2015b; Hughes and Ashton 2016). For example, Lewis et al (2004) found 72% of original biofouling assemblage, including invasive taxa, survived a voyage from Western Australia to Heard Island (sub-Antarctic) and then back to Australia (Tasmania).…”
Section: Discussionsupporting
confidence: 74%
“…For example, Lewis et al (2004) found 72% of original biofouling assemblage, including invasive taxa, survived a voyage from Western Australia to Heard Island (sub-Antarctic) and then back to Australia (Tasmania). More recently, Hughes and Ashton (2016) reported viable individuals of gooseneck ( Conchoderma auritum ) and balanomorph cirripedes on a research ship that travelled from the UK to the Antarctic Peninsula. In contrast, the likelihood of transferring NIS on ship hulls from Arctic to temperate ports seems low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations